From research to reflective teaching (Faculty of Education, UWIMona, Jamaica, 1988)
The papers in this collection all explore ways in which research can be directed to improving practice, thereby bridging the gulf that has long separated researchers and educational practitioners. There are four papers that stress methodological issues, while dealing with a wide range of social interaction in schools; followed by four papers dealing with aspects of the training of teachers and administrators that move more and more in the direction of reflective practice. The volume concludes with a detailed formulation of the argument for self-critical teaching
Special issue of Caribbean Journal of Education, vol. 15, nos. 1&2, 1988
Keywords: Classroom research